2005
DOI: 10.1097/00006982-200510000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoro-N-Octane as a Postoperative Vitreoretinal Tamponade in the Management of Giant Retinal Tears

Abstract: Postoperative tamponade with perfluoro-n-octane may decrease the rate of redetachment in giant retinal tear repair compared with silicone oil or perfluorocarbon gas alone. We found no adverse effects directly attributable to perfluoro-n-octane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 19 publications
5
49
0
2
Order By: Relevance
“…15,28 We observed a high rate (32%) of a characteristic inflammation compared with some previous clinical studies using postoperative PFO for RD. [22][23][24] This may be because of the longer average duration of PFO used in the present study, or underrecognition and retrospective design of previous studies. Rush et al 22 have recently observed inflammation with posterior lens capsule deposits in a comparable proportion (8/39) of eyes with postoperative PFO and reported similar resolution after PFO removal and clinical management with topical corticosteroids.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…15,28 We observed a high rate (32%) of a characteristic inflammation compared with some previous clinical studies using postoperative PFO for RD. [22][23][24] This may be because of the longer average duration of PFO used in the present study, or underrecognition and retrospective design of previous studies. Rush et al 22 have recently observed inflammation with posterior lens capsule deposits in a comparable proportion (8/39) of eyes with postoperative PFO and reported similar resolution after PFO removal and clinical management with topical corticosteroids.…”
Section: Discussionmentioning
confidence: 90%
“…Previous reports have indicated mixed results using heavier-than-water compounds, and previous series investigating PFO 11,[22][23][24]27 have reported small samples of patients with PVR. The results of the present study indicate that a high rate of anatomical success can be achieved with short duration postoperative PFO in advanced PVR.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus far, postoperative perfluoro-n-octane short-term tamponade has been used mainly for retinal detachments caused by giant tears. [5][6][7] Sirimaharaj and associates 6 reported that perfluoro-n-octane was effective for short-term postoperative tamponade to manage retinal detachments resulting from giant retinal tears. They elected to leave the perfluoro-n-octane in situ for 5 to 14 days because doing so provided sufficient time for chorioretinal adhesions to develop.…”
Section: Postoperative Perfluoro-n-octane Tamponade Wasmentioning
confidence: 99%
“…Despite the aforementioned concerns about retinal toxicity, this role has been successfully extended to shortterm postoperative tamponade, with reduced re-detachment rates [35,39]. Here HSO could eventually reduce PVR rates compared to standard silicone oils; however, randomized controlled trials are required to finally solve this question.…”
Section: Heavy Silicone Oil For Various Clinical Applicationsmentioning
confidence: 99%